Crippled by anxiety: Bondage and freedom in the [Lutheran] concept of anxiety. Issue 3 (31st October 2022) - Hockenbery, Jennifer
Abstract: Today's understanding of anxiety has both a clinical and a quotidian sense. This article sketches how both senses owe a debt to Luther's understanding of the distress that arises from the paradoxical human condition of bondage and freedom of the will. While clinical anxiety must be considered in its own right and treated with the most empirically adequate scientific methods available, readers will find that Luther's pastoral views in regard to anxiety speak to the general feelings of anfectung in our current cultural context.